2003
DOI: 10.1046/j.1523-1755.64.s87.8.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of erythropoietin on exercise capacity in anemic patients with advanced heart failure

Abstract: Patients with congestive heart failure (CHF) frequently become anemic. In this review, we will examine the possible etiologies for anemia in heart failure, discuss the cardiovascular consequences of anemia, the effect of anemia on prognosis and exercise capacity, as well as the potential benefits of anemia treatment in this patient population. Etiology of anemia in CHFThe etiology of anemia in patients with congestive heart failure (CHF) is multifactorial and may result from any one or combination of the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 38 publications
1
11
0
1
Order By: Relevance
“…Epo is a multifunctional trophic factor with different sites of endogenous expression, a tissue-specific regulation, and several mechanisms of action (59 -62 MSCs may be similar to that of intermittent pulsed rhEpo, there may be additional clinical benefit on organ systems that express the Epo receptor, such as on myocardium. Epo's many effects include cardioprotection and improved myocardial function (62,(65)(66)(67). Therefore, the greater swimming time in CRF mice that received Epo-secreting MSCs may have arisen not only from the resulting increase in Hct but also from a direct biologic effect on myocardium that would be observed in a setting of continuous Epo delivery, such as provided by our neo-organoid system.…”
Section: Discussionmentioning
confidence: 99%
“…Epo is a multifunctional trophic factor with different sites of endogenous expression, a tissue-specific regulation, and several mechanisms of action (59 -62 MSCs may be similar to that of intermittent pulsed rhEpo, there may be additional clinical benefit on organ systems that express the Epo receptor, such as on myocardium. Epo's many effects include cardioprotection and improved myocardial function (62,(65)(66)(67). Therefore, the greater swimming time in CRF mice that received Epo-secreting MSCs may have arisen not only from the resulting increase in Hct but also from a direct biologic effect on myocardium that would be observed in a setting of continuous Epo delivery, such as provided by our neo-organoid system.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies investigated a correlation between anemia and HF severity and showed that there was an improvement in the ejection fraction (EF), functional class and exercise capacity when anemia improved [24][25][26] .…”
Section: Discussionmentioning
confidence: 99%
“…Çalışmamızda hastaların yarıya yakınında anemi gözlenmiştir. Kalp yetersizliği olan hastalarda aneminin tedavi edilmesi ile kalp fonksiyonlarında ve hastanın egzersiz kapasitesinde düzel-me, hastaneye yatış sayısında ve böbrek fonksiyonlarının bozulmasında azalma olduğu bilinmektedir (33,34). Yakın zamanda yayınlanan ve 600.000 adet AKY'li hastanın taburculuk bilgilerinin değerlendirildiği kayıt tarama çalışmasında anemi sıklığı %27.1 olarak saptanmış ve anemi, böbrek yetersizliği ve kan transfüz-yonunun AKY'li hastalarda hastanede kalış süresinin ve hastane içi ölümün bağımsız belirleyicisi oldukları bildirilmiştir (35).…”
Section: Laboratuvar Bulgularıunclassified